The Regionalization of Lumbar Spine Procedures in New York State: A 10-Year Analysis. Issue 2 (January 2016) - Jancuska, Jeffrey; Adrados, Murillo; Hutzler, Lorraine; Bosco, Joseph
Abstract : Study Design: A retrospective review of an administrative database. Objective: The purpose of this study is to determine the current extent of regionalization by mapping lumbar spine procedures according to hospital and patient zip code, as well as examine the rate of growth of lumbar spine procedures performed at high-, medium-, and low-volume institutions in New York State. Summary of background data: The association between hospital and spine surgeon volume and improved patient outcomes is well established. There is no study investigating the actual process of patient migration to high-volume hospitals. Methods: New York Statewide Planning and Research Cooperative System (SPARCS) administrative data were used to identify 228, 695 lumbar spine surgery patients from 2005 to 2014. The data included the patients' zip code, hospital of operation, and year of discharge. The volume of lumbar spine surgery in New York State was mapped according to patient and hospital 3-digit zip code. New York State hospitals were categorized as low, medium, and high volume and descriptive statistics were used to determine trends in changes in hospital volume. Results: Lumbar spine surgery recipients are widely distributed throughout the state. Procedures are regionalized on a select few metropolitan centers. The total number of procedures grew 2.5% over the entire 10-year-period. High-volume hospital caseload increased 50%, from 7253 procedures in 2005 to 10, 915 procedures in 2014. The number of procedures at medium and low-volume hospitals decreased 30% and 13%, respectively. Conclusions: Despite any concerted effort aimed at moving orthopedic patients to high-volume hospitals, migration to high-volume centers occurred. Public interest in quality outcomes and cost, as well as financial incentives among medical centers to increase market share, potentially influence the migration of patients to high-volume centers. Further regionalization has the potential to exacerbate the current level of disparities among patient populations at low and high-volume hospitals. Level of Evidence: 3